DELs Inside Cells. (April 2020) - Roy, Animesh; Kodadek, Thomas
Abstract : DNA-encoded libraries (DELs) comprise large numbers of small molecules, each of which is conjugated to an encoding DNA. Krusemark and colleagues recently described a method to introduce DELs into living cells and recover conjugates that bind to an intracellular target. This proof-of-principle study suggests that it may be feasible to screen DELs against protein targets in their native environment.